2009
DOI: 10.1108/14626000911000992
|View full text |Cite
|
Sign up to set email alerts
|

Training in Thai SMEs

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 39 publications
1
25
0
3
Order By: Relevance
“…This is confirmed by Thassanabanjong et al (2009) [69] who concluded that training is crucial for productivity and quality and that it also influences the effectiveness, efficiency and motivation of the employees. Indeed, entrepreneurial knowledge can have beneficial effects on the entity's growth and profitability [70].…”
Section: Discussionsupporting
confidence: 58%
“…This is confirmed by Thassanabanjong et al (2009) [69] who concluded that training is crucial for productivity and quality and that it also influences the effectiveness, efficiency and motivation of the employees. Indeed, entrepreneurial knowledge can have beneficial effects on the entity's growth and profitability [70].…”
Section: Discussionsupporting
confidence: 58%
“…In addition to the threefold categorisation of HRD characteristics in SMEs above, we observed that significant discussion in the literature focuses on the key barriers preventing SMEs from engaging in formal HRD. Studies highlighted the inverse relationship between firm size and formal HRD provision (Hoque and Bacon, 2008;Kotey and Folker, 2007), coupled with a lack of willingness to invest time and money in such activity (Castany, 2010;Thassanabanjong et al, 2009). The use of technologically-enabled HRD interventions such as e-learning are also not widespread in SMEs (Admiraal and Lockhorst, 2009;Harris, 2009).…”
Section: Characteristics Of Hrdmentioning
confidence: 99%
“…Empirical studies show that firms use training and skill enhancement programs to develop human resources that can respond to the changing business environment by scanning the market and other external sources [69]. Better-trained workers perform more productively, and they are also more motivated, valuable, and ready to take on more responsibility [70]. Human capital is one of the pivotal types of knowledge resource that resides within individual workers [71]; it encompasses both tacit and explicit knowledge, which enhance their ability to generate knowledge that could be used to achieve organizational innovation [68].…”
Section: Managerial Capability and Adaptive Capabilitymentioning
confidence: 99%